Factors Related to Breastfeeding Self-Efficacy in Breastfeeding Mothers in the Working Area of the Dungingi Health Center - Savitri H. Sune; Nurdiana Djamaluddin; Nur Ayun R. Yusuf (Universitas Muhammadiyah Palu, 2026)
Breastfeeding self-efficacy (BSE) is a mother's belief in her ability to breastfeed which plays an important role in the success of exclusive breastfeeding. The low coverage of exclusive breastfeeding in the working area of the Dungingi Health Center shows that there are still various factors that affect the level of confidence of mothers in breastfeeding. This study aims to analyze the relationship between knowledge, maternal attitudes, and family support with BSE in breastfeeding mothers. The research uses a quantitative method with an analytical design through a cross-sectional approach. The research population amounted to 51 primipara breastfeeding mothers with a research sample of 51 respondents obtained using the total sampling technique. Data collection was carried out using questionnaires on knowledge, maternal attitudes, family support, and BSES-SF. Data analysis was carried out using the Fisher Exact test with a significance level of ? = 0.05. The results showed that most of the respondents had good knowledge (86.3%), a positive attitude (88.2%), good family support (70.6%), and a high level of BSE (60.8%). The results of the bivariate analysis showed a relationship between maternal knowledge and BSE (p=0.011), maternal attitudes with BSE (p=0.002), and family support with BSE (p=0.010). The conclusion of this study shows that knowledge, maternal attitudes, and family support are related to BSE in breastfeeding mothers, especially primipara mothers. Therefore, health workers are expected to improve education and involve families in supporting the success of exclusive breastfeeding.